Evaluation of Therapeutic Strategies to Reduce the Number of Thrombotic Events in Patients With Polycythemia Vera and Essential Thrombocythemia - Tremblay, Douglas; Kosiorek, Heidi E.; Dueck, Amylou C.; Hoffman, Ronald (Frontiers in Oncology, 2021)
Thrombosis is the largest contributor to morbidity and mortality in patients with polycythemia vera (PV) and essential thrombocythemia (ET). Our understanding of the risk factors and pathophysiology of thrombosis in PV and ET patients is developing, including recent insights into the role of aberrant platelet-neutrophil interactions, JAK2 mutated endothelial cells and the pro-thrombotic inflammatory milieu. To date, few available therapies have demonstrated the ability to reduce the thrombotic burden in patients with these diseases. Although numerous therapeutic agents have been investigated in both PV and ET patients, few studies are designed to assess their impact on thrombotic events. In this review, we first describe the burden of thrombosis in patients with these myeloproliferative neoplasms (MPNs) and briefly explore their pathophysiologic mechanisms. We then critically assess and summarize the evidence behind currently available therapies with attention towards thrombotic endpoints. Finally, we describe a path forward for clinical research in MPNs that involves surrogate endpoint validation, biomarker development, and clinical trial design strategies in order to accurately assess reduction of thrombotic events when evaluating novel therapies.